Extra-gain of HER2-positive cases through HER2 reassessment in primary and metastatic sites in advanced gastric cancer with initially HER2-negative primary tumours: Results of GASTric cancer HER2 reassessment study 1 (GASTHER1). (January 2016) - Park, Sook Ryun; Park, Young Soo; Ryu, Min-Hee; Ryoo, Baek-Yeol; Woo, Chang Gok; Jung, Hwoon-Yong; Lee, Jeong Hoon; Lee, Gin Hyug; Kang, Yoon-Koo
Abstract: Purpose: The intratumoural heterogeneity of human epidermal growth factor receptor 2 (HER2) expression in gastric cancer is a major challenge when identifying patients who might benefit from HER2-targeting therapy. We investigated the significance of re-evaluation of HER2 status in primary sites and metastatic or recurrent sites in advanced gastric cancer patients whose primary tumours were initially HER2-negative. Patients and methods: In part I of this study, we evaluated the significance of repeat endoscopic biopsy in unresectable or metastatic gastric cancer patients whose tumours were initially HER2-negative. In part II, we examined the HER2 positivity rate in metastatic or recurrent sites in patients whose primary tumours were HER2-negative in biopsy or surgical specimens. Results: In part I (n = 183), we identified patients with HER2-positive tumours for a rescued HER2 positivity rate of 8.7% (95% confidence interval [CI], 4.6–12.8%) that was associated with tumour location (diffuse stomach versus other = 0% versus 11.7%, P = 0.013), Bormann type (IV versus others = 0% versus 11.7%, P = 0.013), and initial biopsy HER2 immunohistochemistry score (0 versus 1 versus 2 = 6.7% versus 15.4% versus 25.0%, P = 0.028). Part II (n = 175) resulted in HER2 positivity of 5.7% (95% CI 2.3–9.1%) that was significantly associated with metastatic site (liver versus others = 17.2% versus 3.4%, P = 0.012). When compared with a historical control that showed HER2 positivity on initial assessment, patients who had rescued HER2 positivity had similar treatment benefits from trastuzumab-containing first-line chemotherapy. Conclusion: Repeat HER2 assessment in primary and metastatic or recurrent sites is recommended in patients with advanced gastric cancer whose primary tumour is initially HER2-negative. Highlights: The intratumoural heterogeneity of human epidermal growth factor receptor 2 (HER2) status is a major challenge. We reassess HER2 in primary and metastatic sites in initially HER2(–) gastric cancer. Reassessment finds 8.7% (primary sites) and 5.7% (metastatic sites) HER2(+) disease. Patients with rescued HER2(+) have benefits from trastuzumab-containing therapy. We find significant clinical factors associated with rescued HER2 positivity.